2018
DOI: 10.14740/wjon1129w
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of Lung and Bronchial Carcinoid Presenting as Double Synchronous Primary Lung Cancer: A Case Report and Review of Literature

Abstract: Recent advances in imaging techniques led to an increase in the incidence of synchronous and metachronous primary lung cancers due to early detection. Management of these patients is challenging and prognosis depends on the stage of the tumor at initial diagnosis and histological type. A 68-year-old African American male patient with medical history of hypertension and diabetes mellitus presented to our emergency department with right sided chest pain, worsening dyspnea and dry cough of 2-week duration. He als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Postoperative pathological examination showed that the tumor was a collision tumor composed of micropapillary adenocarcinoma and typical carcinoid. Saladi et al [15] reported an elderly male cachexia patient with massive pleural effusion in the right lung in 2018. No cancer cells were found in the right pleural effusion puncture.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pathological examination showed that the tumor was a collision tumor composed of micropapillary adenocarcinoma and typical carcinoid. Saladi et al [15] reported an elderly male cachexia patient with massive pleural effusion in the right lung in 2018. No cancer cells were found in the right pleural effusion puncture.…”
Section: Discussionmentioning
confidence: 99%
“…This is why we choose to sample not only the mass but also the areas of consolidation, which showed, in contrast, an indistinctive margin, no bronchial obstruction and diffusion throughout the lungs. All these latter characteristics are typical of PLA [26,27]; however, the coexistence of a pulmonary carcinoid and PLA has rarely been reported [28][29][30][31]. It is still unclear whether identification of sMPLC in resected specimens (including a comprehensive histological assessment) can be applied to limited preoperative biopsy samples, but performing multiple biopsies on different lung sites during bronchoscopy could be particularly useful, especially in the presence of different endoscopic characteristics of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In one, the authors described a case of combined lung tumor that contained both squamous cell carcinoma and typical carcinoid tumor [ 3 ]. Sen and and Borczuk and Saladi et al documented synchronous lung tumors that comprised both adenocarcinoma and typical carcinoid tumors [ 1 , 4 ]. Furthermore, Yamagata et al described a case of a laryngeal tumor consisting of both squamous cell and atypical carcinoid tumor components [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cases of synchronous but discordant histology with small cell and non-small cell lung carcinoma (NSCLC) occurring in the same patient are rarely reported. To date, there are only a few reported cases of synchronous lung tumors consisting of both NSCLC and carcinoid tumors in the medical literature [ 1 ]. Metachronous tumors are tumors that are also histologically different from one another but occur at different times in the patient.…”
Section: Introductionmentioning
confidence: 99%